Immune Checkpoint Inhibitors: New Weapons Against Medullary Thyroid Cancer? - Di Molfetta, Sergio; Dotto, Andrea; Fanciulli, Giuseppe; Florio, Tullio; Feola, Tiziana; Colao, Annamaria; Faggiano, Antongiulio (Frontiers in Endocrinology, 2021)
Medullary thyroid carcinoma is a rare neuroendocrine neoplasm that originates from thyroid C cells. Surgery, with complete resection of the tumour, is the only curative approach. However, in most cases, the tumour recurs at locoregional or metastatic level. In this setting, the management remains challenging. In recent years, the immune checkpoint inhibitors have provided promise for changing the cancer treatment paradigm through the application of new approaches that enhance the body’s natural antitumour defenses. The aim of this review is to summarize and discuss available data on efficacy and safety of the Food and Drug Administration-approved immune checkpoint inhibitors in patients with medullary thyroid carcinoma. After an extensive search, we found 7 useful data sources (one single-case report, one short article with very preliminary data, five ongoing registered clinical trials). Despite the lack of published evidence regarding the use of immune check point inhibitors, it must be considered that all the ongoing registered clinical trials saw first light in the last three years, thus indicating a growing interest of researchers in this field. Results coming from these trials, and hopefully, in the next future, from additional trials, will help to clarify whether this class of drugs may represent a new weapon in favor of patients with medullary thyroid carcinoma.